2020
DOI: 10.3390/su12166662
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Effect of Mean and Volatility Spillover between the United States Economic Policy Uncertainty and WTI Crude Oil Price

Abstract: Grounded in the Granger causality test, vector autoregression (VAR) model, and BEKK-GARCH model, our current study aims to examine the effect of mean and volatility spillover between the United States (US) economic policy uncertainty (EPU) and West Texas Intermediate (WTI) crude oil price. Using the US EPU monthly index and WTI spot price data from 1996 to 2019, we revealed that there is a one-way Granger causality link between the US EPU and spot price of WTI crude oil. The VAR model not only illustrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The research results presented in this paper also contribute to the work of policymakers [37] because the WT-FNN model results indicated that recent data contained more useful information than historic data for crude oil price prediction. Therefore, policy makers should not focus on similar events in history when forecasting crude oil prices but should pay more attention to recent events and assess their influence on crude oil prices to predict crude oil prices more accurately.…”
Section: Discussion Of the Results And Conclusionmentioning
confidence: 66%
See 1 more Smart Citation
“…The research results presented in this paper also contribute to the work of policymakers [37] because the WT-FNN model results indicated that recent data contained more useful information than historic data for crude oil price prediction. Therefore, policy makers should not focus on similar events in history when forecasting crude oil prices but should pay more attention to recent events and assess their influence on crude oil prices to predict crude oil prices more accurately.…”
Section: Discussion Of the Results And Conclusionmentioning
confidence: 66%
“…In this paper, we used the previous 4 days' crude oil prices to predict crude oil prices on the 5th day; therefore, the number of input layer neurons was four. According to [36,37], when the number of hidden layer neurons is half the number of input layer neurons, the predictive effect is best. Therefore, we determined that the number of input layer neurons was four, the hidden layer was two, and the output layer was one; that is, crude oil prices on the fifth day were predicted by the crude oil prices of the previous 4 days.…”
Section: Different Neuronsmentioning
confidence: 99%
“…Energy prices (Karstensen and Peters 2018), gross domestic product (GDP) (Liu et al 2023) and total carbon emissions (Green 2021) play an important role in predicting the CEA prices. The West Texas Intermediate (WTI) crude oil has become the worldwide standard for crude oil pricing due to the global military as well as economic power of the United States (Su et al 2020). Eviews (Econometric Views) software is one of the most popular econometric software for the rapid creation, estimation, testing and application of econometric models of the quantitative laws of socioeconomic relations and economic activities (Xie 2023).…”
Section: Carbon Emissions Allowances (Ceas) Prices Projectionmentioning
confidence: 99%
“…Previous research has established that a variety of geopolitical risk events, such as macroeconomic announcements [15,35,36], significant political occurrences [20,37], and economic policy uncertainties [14,38], affect asset price returns. Geopolitical risk, as defined by [39], refers to the "efforts of states and organizations to assert control and vie for territory...the risks arising from wars, acts of terrorism, and tensions between states that disrupt the usual and peaceful progression of international relations".…”
Section: Spillover Of Geopolitical Events On Oil Stock Returnsmentioning
confidence: 99%